How does culture affect the entrepreneurial process? A comparative analysis of Gulf and European Countries - Khoja, Ohoud Khaled (Journal of Educational and Psychological Sciences, 2021)
The objective of this study was to determine if culture as represented by countries from the Gulf and Europe affects the entrepreneurial process.  Entrepreneurship is important for wealth creation, job creation and improving economic prosperity. By better understanding how culture affects the ability of entrepreneurs to prosper, business and government policy can be designed to facilitate this. This study therefore aims to fill the gap in knowledge which currently exists on the effects of culture on the entrepreneurial process. The relationships between cultural dimensions, individual entrepreneurial talent and entrepreneurial outcomes were tested using a cross-sectional self-report survey design among a sample of European and Gulf-based entrepreneurs (n=84). Previously validated scales were utilised to elicit ratings for cultural-orientation (CVSCALE) and individual entrepreneurial tendencies (META).  ANOVA revealed no significant main effect of culture on entrepreneurial outcomes, but regression analysis confirmed the positive association of individual abilities on business longevity, size and growth in the European context.  META was found to have a positive effect on revenue and profit in both regions, although this was only significant in respondents from Europe.  Regression analysis confirmed a moderating effect of culture on the relationship between entrepreneurial talent and business success.  Whereas uncertainty-avoidance emerges as the main moderator of this effect in the European sample, the collectivism cultural-orientation is found to strongly moderate the relationship between META and business size, history and growth in the Gulf region.  These mixed findings are interpreted as supporting the proposition by Shane et al. (1995) that entrepreneurial success is contingent on the match between background culture and individual propensity.  In line with Ajzen’s (1991) Planned Behavior Theory these findings are explained in terms of the direct and indirect impact of culture on entrepreneurial intentions and behavior.
Keywords: Entrepreneurial potential; Cultural dimensions; Gulf and European countries; Propensity